3(x+2)+11>20
minus 11 both sides
3(x+2)>9
divide both sides by 3
x+2>3
minus 2 both sides
x>1
Well, "minus 6 x cubed minus y squared minus 3 x y" translates to:
![-6x^{2} -y^{2} -3xy](https://tex.z-dn.net/?f=-6x%5E%7B2%7D%20-y%5E%7B2%7D%20-3xy)
Then, if we insert the values for x and y, we get:
![-6(-2)^{2} -(4)^{2} -3(-2)(4)](https://tex.z-dn.net/?f=-6%28-2%29%5E%7B2%7D%20-%284%29%5E%7B2%7D%20-3%28-2%29%284%29)
When we distribute and multiply:
![144-16-24](https://tex.z-dn.net/?f=144-16-24)
And once we combine like terms:
104<em> is the answer</em>
Answer:
![\frac{1}{2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B2%7D%20)
Step-by-step explanation:
slope :
= 0.5
Y=kx
12=-4k
k = -3
so when y = 15
y = kx
15 = -3x
x = -5
----------------
$50 / 0.04 = $1250 (4% interest)
so
1250 * 0.06 = $75
answer
interest $75 at 6%
-----------------------------
y = kx
1/4 = 4k
k = 1/16
when x = 5
y = kx
y = 1/16(5)
y = 5/16
-----------
y = kx
-5 = 4k
k = -5/4
direct equation
y = -5/4x